MAKNA VISUAL PADA BOOK COVER NOVEL BUMI KARYA TERE LIYE - Juliana fatma Amran; Zubaidah A Zubaidah A (Universitas Negeri Padang, 2020)
On the earth cover book written by Tereliye, there are found many signs and visual language that need to be explored deeper. Another thing that was found was related to the pictures and components of the book cover with the fiction storyline on earth novels. The purpose of this study is to analyze the meaning and also the relationship of the book cover with the storyline in Tereliye's Eart novel.The research method used by researchers is a type of descriptive qualitative method with literature study data collection techniques where the data obtained from various sources of books, journals and the internet. This study uses a semiotic theory approach and color theory and also the theory of visual elements in the object of research, namely Tereliye's book cover earth. This study describes the pieces of the picture and the description of the data in the form of data denotation and connotation to clarify any meaning that is on the cover book by Tereliye's novel.The results of this study explain that the visuals on the book cover have a connection with the storyline.Keywords: Book Cover, Semiotics, novel